PELATIHAN INTERNET SEHAT SEBAGAI MEDIA PEMBELAJARAN BAGI GURU - Stefani Made Ayu Artharini Koesanto; Rahmaddian Rahmaddian (Dharma Duta, 2020)
Giving messages or information seems to be a habit, yet at the same time become a liaison between people each other throughout the world from one single access platform. Interactivity on internet which has more value in giving, receiving and even editing and commenting on the information rather than offline communication becomes the main attraction for the global community. Most people are using internet as it is become daily basis phenomena around the world. The flood of information about the unknown event will kindly occurs, even though the news that is displayed is only a few and bits - the slightest news will still be needed when the lack of information happen. TI is not surprising when a terror event occurs, the flood of information is so overwhelming in various media, because everyone is able to be a provider of information by post it quickly and easily everywhere, online. The purpose of this service is to provide training, giving information and at the same time sharing experiences related to the healthy internet as a learning media for teachers at SMAN-1 Kuala Kapuas. The training methods used in this service are the lecture, discussion and practice methods. Based on the results of the evaluation, all training/outreach participants are having a better understaning about the importance of using the internet in a healthy manner as a learning media.